Forest litter decomposition stimulates heterotrophic nitrogen fixation by driving diazotrophic community interactions - Pan, Chang; Bei, Shuikuan; Hua, Zhe; Zhou, Mengtian; Wang, Zichen; Fu, Ruoxian; Li, Xiaogang (Biology and fertility of soils, 2025)
The decomposition of carbon-rich litter in forest ecosystems is thought to regulate critical nutrient cycles, including biological N fixation. However, the dynamics of N fixation and its driving mechanisms during litter decomposition remain elusive. In the present study, we tracked N fixation rate (NFR), diazotrophic community characteristics and associated soil factors during the decomposition of Chinese fir and/or Schima superba leaf litter in a 60-day microcosm experiment. Soil NFR significantly increased as the litter addition and the incubation time, but it was not affected by litter types. Diazotrophic community interactions and key diazotroph species, identified by co-occurrence network, were changed as litter decomposition progressed. NFR was significantly correlated with the richness of putative key diazotrophs, and was mainly mediated by changes in soil NH 4 + -N, and key C fractions of organic C. Structural equation modeling further revealed that the intensification of soil N fixation functions during litter decomposition was mediated by complex diazotrophic interactions rather than community diversity.